MSMEs and their role in encouraging sustainable healthy diets in Viet Nam - de Brauw, Alan; Huynh, Tuyen; Dao The Anh; Pham Thi Hanh Tho; Truong Tuyet Mai (International Food Policy Research Institute, 2025)
In this brief, we explore diet quality gaps in survey data collected in a transect of locations in Vietnam, including an urban district, a peri-urban district, and a rural district. We find that healthy foods are relatively underconsumed, at least among adolescents. We find that when households report purchasing most types of healthy foods, they buy them from MSMEs. Among types of healthy foods that are underconsumed, we find they are most commonly available at small groceries. Therefore, as Vietnam begins to implement policies to guide food systems transformation at the subnational level, it would seem worthwhile to target small groceries as a conduit for selling more components of healthy diets. De Brauw, Anh and Pham (2024) find that some business skills are particularly lacking among small groceries; for example, they find that very few small groceries have financial records, record sales, or have a written budget. Small groceries also lack access to finance. However, many of them also sell less healthy foods, such as refined grains (such as white rice), sweets, and sugar sweetened beverages. Therefore it is important to combine any business skills with nutrition education, to try to ensure that business owners do not use newfound skills to promote the sale of additional unhealthy products. There are several policy levers, existing at both the national and provincial levels, that could be used to help MSMEs sell more healthy products. However, it is important to monitor these policies to ensure that they are catalyzing food systems transformation towards healthy diets. With appropriate training and potentially additional finance, MSMEs selling healthier foods can be encouraged to grow and improve the accessibility of healthy foods.